Status of Seaweed K. alvarezii Cultivation Sustainability as a Strategic Direction for Seaweed Management in Baubau City, Southeast Sulawesi - Nurul Annisa; Muhammad Farid Samawi; M. Rijal Idrus (Postgraduate, University of Mataram, 2023)
This study aims to examine its sustainability status. This study used survey techniques and interviews with seaweed cultivators to collect data. Sustainability data on seaweed cultivation include social, economic, and ecological aspects. The Rapseaweed approach (Rapid Appraisal for Seaweed) has been modified from Rapfish (Rapid Appraisal for Fisheries) to evaluate the sustainability status of seaweed in a multidisciplinary manner. Analysis of the sustainability of K. alvarezii seaweed cultivation using the MDS method. The Rapseaweed analysis reveals that the ecological sustainability index value is 57.76, and the availability of seeds is the most sensitive attribute, with a change in root mean square RMS value of 4.59. Seaweed marketing is the most sensitive attribute, with a change in root mean square RMS value of 12.96, and the economic dimension index value is 65.62. The cultivator's habits have the highest index value of 69.75% for the social dimension, with a root mean square RMS change value of 10.47. All dimensions are considered to be